Effect of small-sided games on the biochemical profile of elite soccer players - Mitrotasios, M.; Souglis, A.; Gioldasis, A.; Ispyrlidis, I.; Mantzouranis, N.; Andronikos, G. (Journal of Physical Education and Sport, 2021)
In soccer players are exposed to intensive physiological stress during training, which promote changes in biochemical markers that practitioners have to investigate in order to determine the internal training load. In this sense soccer training mainly due to eccentric actions cause biochemical disturbances that increase inflammation and muscle damages which may reduce performance. A popular training method which is widely used by soccer practitioners to optimize training time by replicating games` demands, is Small Sided Games (SSGs). Thus, the aim of this study was to examine lipid, enzyme, and hormone changes caused by Small Sided Games (SSGs). The sample consisted of eight U20 elite soccer players (aged 18.3 ± 1 year) of the Greek Super League, who participated in six SSG`s (4 vs 4 + 2 GK) each lasting 4 min with rest of 3 min, on an artificial field with dimensions of 30x20m. Blood samples were taken by accredited personnel before and after the six SSGs to determine the change of the lipid profile, enzymes, and hormones. The Total Cholesterol (T-C), High density lipoprotein cholesterol (HDL-C), Low density lipoprotein cholesterol (LDL-C), Triglycerides (TG), Lipid, gamma-glutamyltransferase (?-GT), Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Plasma Creatine Kinase (CK), Isoenzyme of creatine kinase (CK-MB), Lactate dehydrogenase (LDH), Cortisol, Testosterone were measured. The Wilcoxon Test (Z) and the Effect Size (r) were used to compare the repeated measures of the variables (pre and post), while the Pearson correlation (r) was used to test the correlation between them. The results showed that T-C, HDL-C, T-C/HDL-C (ratio), LDL-C, and TG were non- significantly reduced after the interventional SSGs. On the contrary, CK, CK-MB, LDH and Testosterone significantly reduced due to the interventional SSGs, whereas Cortisol significantly increased. Overall, the results showed that SSGs with high intensity cause specific metabolic effects of the enzyme and hormonal profile on male players. Understanding the importance of the impact of lipid parameters for the performance and health of the players can help coaches and to better prepare high-intensity training sessions.